Comparing the Effectiveness of a Matching Quiz and Half-Minute Paper as Formative Assessment Tools - Refnita, Lely; Jufrizal, Jufrizal (KnE Social Sciences, 2022)
A range of research studies have been conducted on either quizes or minute papers as formative assessment tools. A comparison of both tools was done by Kwan through his survey of students learning about the principles of economics. Kwan’s study compared the application of a one-minute paper and quiz in the form of extended true-false, multiple-choice, and short answers. However, this article experimentally compared a matching quiz and half-minute paper as formative assessment tools in an Educational Research Design class, a content-based subject taught to university students. The results of the descriptive statistics showed that the matching quiz was more effective than the half-minute paper as a formative assessment tool. Inferential statistics using the independent sample t-test, however, revealed that the difference between the experimental and control groups’ posttest mean scores was not statistically significant. This indicated that the matching quiz and half-minute paper could possibly be used interchangeably; however, the teacher should be aware that the matching quiz is more practical but cannot develop students’ higher-order thinking skills, while the half-minute paper encourages active learning but takes more time to apply. Keywords: effectiveness, matching quiz, half-minute paper, formative assessment